Análisis de la morosidad en las instituciones microfinancieras (IMF) en el ~ e r - Aguilar Andía, Giovanna (2002)
The main objective  of  this research is to identify the variables that  affect the Peruvian Microfinance Institutions' (MFI) delinquency. The  relative irnportance of  three kinds of variables is analyzed. First,  aggregate  or  macroeconomic  variables related  to  Peruvian  economic  activity (GDP, inflation, etc.). Second, microeconomic variables  related to the management policy of  the  MFI (credit policy, credit technology,  incentives sys- tem to employees, etc.). And finally, variables related to the  local dynamics of  markets where MFI  make their business (regional GDP,  dynamics of  local finance market, local productive activity,  etc.). An  unbalanced dynamic  model of  panel data for  35  MFI with monthly data in the period  1998-2001 is  estimated  using the Generalized  Method of  Moments estimation technique.